1997
DOI: 10.1007/bf02311703
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of muscimol, a potent GABAA receptor agonist, crystal structure and quantum chemicalab initio calculations

Abstract: Muscimol, a constituent of the mushroom Amanita muscaria, is a semirigid analogue of the inhibitory neurotransmitter 4-aminobutyric acid (GABA). X-ray structure determinations and quantum chemical ab initio calculations (HF/6-3 IG*) have been carried out on the muscimol zwitterion. The solid-state conformations of the muscimol zwitterion are calculated to be 1.6-2.2 kcal/ mol higher in energy than that of the calculated minimum energy structure in vacuo. A comparison of the calculated and experimental structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…The Cambridge Structural Database was consulted for coordinates for muscimol (CSD code: MUSIMO01) [10], flunitrazepam (CSD code: CAGWUC) [15] and alprazolam (CSD code: CIZQAD01) [72]. The coordinates of halothane were generated ab initio and its geometry optimised according to the potential of Scharf and Laasonen [77].…”
Section: Ligand Dockingmentioning
confidence: 99%
“…The Cambridge Structural Database was consulted for coordinates for muscimol (CSD code: MUSIMO01) [10], flunitrazepam (CSD code: CAGWUC) [15] and alprazolam (CSD code: CIZQAD01) [72]. The coordinates of halothane were generated ab initio and its geometry optimised according to the potential of Scharf and Laasonen [77].…”
Section: Ligand Dockingmentioning
confidence: 99%
“…Its crystal structure proves the presence of a zwitterion form (a) of muscimol in the solid state. This structure was also supported by low level ab initio calculations .…”
Section: Introductionmentioning
confidence: 90%
“…For instance, it has been shown that replacement of the 3-isoxazolol ring in these molecules by an isothiazolol ring (e.g., compound 25) has significantly different effects on the receptor affinity [72,83,109]. Furthermore, high-level quantum chemical ab initio calculations indicate that the assumed THIP-like bioactive conformation of muscimol has a very high conformational energy [110], which is not compatible with its high affinity. Furthermore, high-level quantum chemical ab initio calculations indicate that the assumed THIP-like bioactive conformation of muscimol has a very high conformational energy [110], which is not compatible with its high affinity.…”
Section: Receptor and Pharmacophore Models Of The Gaba Site Of The Gamentioning
confidence: 99%